Manganese-rich sodium ion positive electrode material and preparation method and application thereof

By incorporating lithium/potassium and M-C-based nanomaterials into the manganese-rich sodium ion positive electrode material, the problem of poor structural deterioration and poor circulation performance of the material at high voltage is solved, and good cycle stability and safety performance are achieved.

CN114242973BActive Publication Date: 2025-02-07GUANGDONG BRUNP RECYCLING TECH CO LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111441742.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-30
Publication Date
2025-02-07
Estimated Expiration
2041-11-30

AI Technical Summary

Technical Problem

The existing structure of manganese sodium-rich positive electrode materials tends to become irregular under high voltage, with poor circulation performance, and a large Na+ radius leads to poor structural stability of the material during the deflection process, resulting in significant attenuation of the battery circulation capacity.

Method used

Na(ZkNitMnf)O2/M-C is used as the sodium ion positive electrode material, and the sodium-to-lithium/potassium ratio is adjusted by incorporating lithium/potassium to inhibit the mixed discharge of sodium-manganese, and the material is coated by adding M-C-based nanomaterials. The peeling and structural phase change of the oxide layer are inhibited.

Benefits of technology

The cycle stability and safety performance of sodium ion positive electrode material is improved, the tap density and specific capacity of the material are enhanced, the structural phase change is suppressed, and the circulation capacity of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114242973B_ABST
    Figure CN114242973B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of sodium ion batteries, and discloses a manganese-rich sodium ion positive electrode material and a preparation method and application thereof. The general formula of the sodium ion positive electrode material is Na(Z k Ni t Mn f )O2 / M‑C, k+t+f=1,0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium-ion batteries, and particularly relates to a sodium-ion cathode material rich in manganese, a preparation method thereof, and an application thereof. Background Art

[0002] Currently, in the research of sodium-ion battery cathode materials, there is more research on sodium-ion cathode materials rich in manganese. However, there are some deficiencies in sodium-ion cathode materials rich in manganese. First, the performance of sodium-ion cathode materials rich in manganese is worse than that of lithium-ion batteries of the same type rich in manganese. Second, due to the relatively high voltage window of sodium-ion cathode materials rich in manganese, the structure of the material is prone to irreversible deformation at high voltages, and the structure is extremely likely to become irregular, resulting in poor cycling performance. Moreover, because the radius of Na + is relatively large, the stability of the material structure will deteriorate during the insertion and extraction process, resulting in obvious attenuation of the battery cycle capacity. Summary of the Invention

[0003] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. For this purpose, the present invention provides a sodium-ion cathode material rich in manganese, a preparation method thereof, and an application thereof. The sodium-ion cathode material rich in manganese has good cycle stability and excellent safety performance.

[0004] To achieve the above object, the present invention adopts the following technical solutions:

[0005] A sodium-ion cathode material, whose general formula is Na(Z k Ni t Mn f )O 2 / M-C, where k + t + f = 1, 0 < k ≤ 0.3, 0 < t ≤ 0.5, 0.4 ≤ f < 1, and Z is at least one of K and Li; M is at least one of Cu and Zn.

[0006] Preferably, the general formula of the sodium-ion cathode material is Na(Z k Ni t Mn f )O 2 / M-C, where k + t + f = 1, 0 < k ≤ 0.25, 0.10 ≤ t ≤ 0.5, 0.4 ≤ f ≤ 0.8, and Z is at least one of K and Li; M is at least one of Cu and Zn.

[0007] Preferably, the sodium-ion cathode material is Na(K 0.058 Ni 0.192 Mn 0.75 )O 2 @Cu-C, Na(K 0.208 Ni 0.192 Mn 0.60 )O2 @Cu-C、Na(K 0.117 Ni 0.233 Mn 0.65 ) 2 @Zn-C、Na(Li 0.053 K 0.053 Ni 0.164 Mn 0.73 ) 2 @Zn-C、Na(Li 0.10 K 0.04 Ni 0.46 Mn 0.40 ) 2 @One of Zn-C.

[0008] A method for preparing a sodium ion positive electrode material, wherein the method is used to prepare the above-mentioned sodium ion positive electrode material.

[0009] Specifically, a method for preparing a sodium ion positive electrode material comprises the following steps:

[0010] Mix manganese salt and nickel salt, add precipitant, react, separate solid and liquid, take solid phase, add sodium potassium or sodium lithium solution, mix, sinter, and obtain Na(Z k Ni t Mn f ) 2 ;

[0011] The Na(Z k Ni t Mn f ) 2 Adding the mixture into methanol containing an ammonium source and mixing the mixture to perform surface reduction, thereby obtaining a surface-reduced sodium ion positive electrode material;

[0012] The surface-reduced sodium ion positive electrode material is mixed with the MC-based nanomaterial and calcined to obtain the sodium ion positive electrode material.

[0013] Preferably, the manganese salt is at least one of manganese sulfate, manganese nitrate and manganese chloride.

[0014] Preferably, the nickel salt is at least one of nickel sulfate, nickel nitrate and nickel chloride.

[0015] Preferably, the precipitant is at least one of sodium carbonate, lithium carbonate and carbonic acid.

[0016] Preferably, the sodium-potassium or sodium-lithium solution is prepared by dissolving a sodium source, a potassium source or a lithium source in water to obtain a sodium-potassium, sodium-lithium or sodium-potassium-lithium solution.

[0017] Further preferably, the sodium source is at least one of sodium hydroxide, sodium acetate, sodium carbonate, sodium phosphate and sodium citrate.

[0018] Further preferably, the lithium source is at least one of lithium hydroxide, lithium formate, lithium acetate, lithium carbonate, lithium nitrate, lithium oxalate, lithium sulfate or lithium chloride.

[0019] Further preferably, the potassium source is at least one of potassium hydroxide, potassium formate, potassium acetate, potassium carbonate, potassium nitrate, potassium oxalate, potassium sulfate or potassium chloride.

[0020] Further preferably, the molar ratio of manganese in the manganese salt, nickel in the nickel salt, lithium in the lithium source, and potassium in the potassium source is (40-100):(0.01-60):(0.01-30):(0.01-10).

[0021] Preferably, the sintering temperature is 400-1100° C., and the sintering time is 3-12 hours.

[0022] Preferably, the proportion of ammonium source in the methanol containing ammonium source is 0.001-5%.

[0023] Further preferably, the ammonium source is at least one of ammonia, ammonium sulfate, ammonium chloride, ammonium nitrate and ammonium formate.

[0024] The cooling is due to the absorption of water and ammonium radical decomposition products by methanol.

[0025] Preferably, the methanol containing an ammonium source and Na(Z k Ni t Mn f ) 2 The liquid-to-solid ratio is (0.1-10):(1-5)mL / g.

[0026] Preferably, the surface reduction temperature is 200-400°C.

[0027] Preferably, the surface reduction atmosphere is a rare gas; the rare gas is at least one of Ne, Kr, and Ar.

[0028] Preferably, after the surface reduction, the sodium ion positive electrode material is further cooled, washed, demagnetized and dried.

[0029] Further preferably, the demagnetization is performed by using a demagnetization rod.

[0030] Preferably, the MC-based nanomaterial is prepared by mixing a complexing agent and a polar organic matter, and then dropping the mixture into a solution containing M ions, stirring the mixture, standing the mixture, centrifuging the mixture, and drying the mixture to obtain the MC-based nanomaterial.

[0031] Further preferably, the volume ratio of the M-containing solution, the complexing agent, and the polar organic matter is (0.05-15):(0.1-20):(1-20).

[0032] More preferably, the complexing agent is at least one of salicylic acid and terephthalic acid.

[0033] Further preferably, the polar organic matter is at least one of ethylene glycol, acetone, acetic acid or petroleum ether.

[0034] Further preferably, the M-containing solution is at least one of a copper nitrate solution and a zinc nitrate solution.

[0035] Preferably, the amount of the MC-based nanomaterial added accounts for 0.01-10% of the mass of the surface-reduced sodium ion positive electrode material.

[0036] More preferably, the standing time is 3-12 hours.

[0037] More preferably, the drying temperature is 60-120° C., and the drying time is 15 min-8 h.

[0038] Preferably, before the calcination, the process further comprises ball milling a mixture of the surface-reduced sodium ion positive electrode material and the MC-based nanomaterial.

[0039] Preferably, after the calcination, the sodium ion positive electrode material is further subjected to cooling, washing and drying.

[0040] Preferably, the calcination temperature is 300-900° C., and the calcination time is 2-12 hours.

[0041] Preferably, the calcination atmosphere is oxygen or air.

[0042] The present invention also provides a battery, comprising the sodium ion positive electrode material.

[0043] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0044] 1. The manganese-rich sodium ion positive electrode material Na(Z k Ni t Mn f ) 2 / MC (Z is Li or K) is doped with lithium / potassium to adjust the ratio of sodium to lithium / potassium, inhibit the sodium-manganese mixing phenomenon in the manganese-rich sodium ion positive electrode material, and then the sodium ion positive electrode material is coated by adding MC-based nanomaterials to inhibit the peeling of the oxide layer, reduce the structural phase change of the material during charging and discharging, increase the tap density of the material, and further improve the specific capacity of the material and the effect of inhibiting phase change, thereby ensuring good cycle stability and excellent safety in sodium ion batteries.

[0045] 2. In the preparation method of the present invention, a low proportion of ammonia is added to methanol. Under high temperature conditions, the ammonia in the methanol is released and reacts with oxygen on the surface of the sodium ion positive electrode material to generate nitrogen oxides and H 2 O, resulting in surface oxygen deficiency, while the appropriate number of oxygen vacancies on the surface can serve as electrons and charge carriers. Under the condition of ensuring the structural stability of the positive electrode material, it can reduce the activation energy required for the migration of manganese and nickel ions, and can also promote the sodium ion and electron transport process of the positive electrode material and increase the sodium ion diffusion coefficient. In addition, the added methanol / rare gas can inhibit nitrogen oxides and H 2 The effect of O on the positive electrode material can be absorbed after cooling.

[0046] 3. The present invention improves the synthesis method and the incorporation method, by precipitating manganese nickel with carbonate, adding a sodium source, and incorporating lithium / potassium with a low atomic radius by a liquid phase method, which can not only improve the uniformity of the incorporated lithium / potassium, but also adjust the ratio of sodium to lithium / potassium by the incorporation of lithium / potassium, and inhibit the sodium-manganese mixing phenomenon in the manganese-rich sodium ion positive electrode material, thereby improving the electrochemical performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is a SEM image of the Co-C based nanomaterial prepared in Example 1 of the present invention;

[0048] Figure 2 This is the SEM image of the Cu-C based nanomaterial prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0049] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0050] Example 1

[0051] The sodium ion positive electrode material of this embodiment has the formula Na(K 0.058 Ni 0.192 Mn 0.75 ) 2 @Cu-C.

[0052] The specific steps for preparing the sodium ion positive electrode material of this embodiment are as follows:

[0053] (1) 200 mL of 1.5 mol / L manganese sulfate solution and 208 mL of 0.37 mol / L nickel sulfate solution were mixed in a polytetrafluoroethylene cup, the polytetrafluoroethylene cup was placed in a 50°C water bath, stirred, 230 mL of 1.45 mol / L ammonium was added dropwise until complete precipitation to obtain a manganese-nickel precipitate, the precipitate was separated, 240 mL of 1.73 mol / L sodium hydroxide solution and 1.3 g of potassium hydroxide were mixed to form a sodium-potassium solution, the sodium-potassium solution was added dropwise to the manganese-nickel precipitate, the mixture was fully mixed, dried in an oven at 95°C for 40 min, ball-milled, and calcined at 750°C in a tubular heater for 7 h and 33 min to obtain Na(K 0.058 Ni 0.192 Mn 0.75 ) 2 .

[0054] (2) Weigh 20 g of Na(K 0.058 Ni 0.192 Mn 0.75 ) 2 Add into 20 mL of methanol (ammonia content 0.57%), mix evenly, send to a tubular heater, exhaust, introduce Ar, keep warm at 330°C for 2 h and 18 min, cool to room temperature, wash, demagnetize and dry to obtain a surface-reduced sodium ion positive electrode material.

[0055] (3) Weigh 25 mL of 32.7 w% salicylic acid and 25 mL of propylene glycol and stir them thoroughly, then dropwise add 10 mL of 0.05 mol / L copper nitrate solution, stir, let stand for 4 h and 4 min, centrifuge, and send to a microwave reactor. Evacuate the gas in the reactor, set to 86 ° C for drying, and dehydrate for 60 min to obtain Cu-C-based nanomaterials.

[0056] (4) Weigh 10 g of the surface-reduced sodium ion positive electrode material and 0.25 g of the Cu-C-based nanomaterial, mix and ball-mill, send to a tubular heater, calcine at 660° C. in an air-filled atmosphere for 7 h and 43 min, cool, wash, and dry in an oven at 95° C. for 3 h and 23 min to obtain a coated Na(K 0.058 Ni 0.192 Mn 0.75 ) 2 @Cu-C material.

[0057] Example 2

[0058] The sodium ion positive electrode material of this embodiment has the formula Na(K 0.208 Ni 0.192 Mn 0.60 ) 2 @Cu-C.

[0059] The specific steps for preparing the sodium ion positive electrode material of this embodiment are as follows:

[0060] (1) 320 mL of 0.75 mol / L manganese sulfate solution and 208 mL of 0.37 mol / L nickel sulfate solution were mixed in a polytetrafluoroethylene cup, the polytetrafluoroethylene cup was placed in a 50°C water bath, and stirred. 260 mL of 0.30 mol / L ammonium carbonate was added dropwise until complete precipitation to obtain manganese nickel carbonate precipitate. The precipitate was separated, and 240 mL of 1.73 mol / L sodium hydroxide solution and 4.67 g of potassium hydroxide were mixed to form a sodium potassium solution. The sodium potassium solution was added dropwise to the manganese nickel precipitate, and the mixture was thoroughly mixed, dried in an oven at 95°C for 40 min, ball milled, and calcined at 550°C in a tubular heater for 7 h and 33 min to obtain Na(K 0.208 Ni 0.192 Mn 0.60 ) 2 .

[0061] (2) Weigh 20 g of Na(K 0.208 Ni 0.192 Mn 0.60 ) 2 Add into 20mL methanol (ammonium sulfate content 0.89%), mix evenly, send to a tubular heater, exhaust, introduce Ar, keep warm at 330℃ for 2h and 18min, cool to room temperature, wash, demagnetize and dry to obtain a surface reduced sodium ion positive electrode material.

[0062] (3) Weigh 20 mL of 16.4 w% salicylic acid and 20 mL of propylene glycol and stir them thoroughly, then dropwise add 7 mL of 0.05 mol / L copper nitrate solution, stir, let stand for 4 h and 7 min, centrifuge, and send to a microwave reactor. Evacuate the gas in the reactor, set to 80 °C for drying, and dehydrate for 70 min to obtain Cu-C-based nanomaterials.

[0063] (4) 10 g of the surface-reduced sodium ion positive electrode material was mixed with 0.35 g of Cu-C-based nanomaterial, ball-milled, and sent to a tubular heater, calcined at 660° C. in an air-filled atmosphere for 7 h and 43 min, cooled, washed, and dried in an oven at 95° C. for 3 h and 23 min to obtain a coated Na(K 0.208 Ni 0.192 Mn 0.60 ) 2 @Cu-C material.

[0064] Example 3

[0065] The sodium ion positive electrode material of this embodiment has the formula Na(K 0.117 Ni 0.233 Mn 0.65 ) 2 @Zn-C.

[0066] The preparation method of the sodium ion positive electrode material of this embodiment has the following specific steps:

[0067] (1) 347 mL of 0.75 mol / L manganese sulfate solution and 252 mL of 0.37 mol / L nickel sulfate solution were mixed in a polytetrafluoroethylene cup, and then placed in a 50°C water bath and stirred. 260 mL of 0.30 mol / L ammonium carbonate was added dropwise until complete precipitation to obtain manganese carbonate nickel precipitate. The precipitate was separated, and 410 mL of 1.0 mol / L sodium citrate solution and 2.63 g of potassium hydroxide were mixed to form a sodium potassium solution. The sodium potassium solution was added dropwise to the manganese nickel precipitate, and the mixture was fully mixed, dried in an oven at 100°C for 45 min, ball milled, and calcined at 680°C in a tubular heater for 7 h and 7 min to obtain a sodium ion positive electrode material Na(K 0.117 Ni 0.233 Mn 0.65 ) 2 .

[0068] (2) Weigh 20g Na(K 0.058 Ni 0.192 Mn 0.75 ) 2 Add into 30mL methanol (ammonium sulfate content 0.89%), mix evenly, send to a tubular heater, exhaust, introduce Ar, keep warm at 240℃ for 3h and 15min, cool to room temperature, wash, demagnetize and dry to obtain a surface reduced sodium ion positive electrode material.

[0069] (3) 25 mL of 32.7 w% salicylic acid and 25 mL of propylene glycol were fully stirred, and 10 mL of 0.05 mol / L zinc nitrate solution was added dropwise, stirred, allowed to stand for 4 h and 4 min, centrifuged, and sent to a microwave reactor. The gas in the reactor was evacuated, and the temperature was set to 86 ° C for drying and dehydration for 60 min to obtain Zn-C-based nanomaterials.

[0070] (4) 10 g of the surface-reduced sodium ion positive electrode material was mixed with 0.45 g of Zn-C-based nanomaterial, ball-milled, and sent to a tubular heater for calcination at 760° C. in an air atmosphere, cooled, washed, and dried in an oven at 100° C. for 3 h and 2 min to obtain a coated Na(K 0.058 Ni 0.192 Mn 0.75 ) 2 @Zn-C material.

[0071] Example 4

[0072] The sodium ion positive electrode material of this embodiment has the formula Na(Li 0.053 K 0.053 Ni 0.164 Mn 0.73 ) 2 @Zn-C.

[0073] The preparation method of the sodium ion positive electrode material of this embodiment has the following specific steps:

[0074] (1) 273 mL of 1.07 mol / L manganese sulfate solution and 355 mL of 0.185 mol / L nickel sulfate solution were mixed in a polytetrafluoroethylene cup, and then placed in a 50°C water bath and stirred. 260 mL of 0.30 mol / L ammonium carbonate was added dropwise until complete precipitation to obtain a manganese nickel precipitate. The precipitate was separated, and 410 mL of 1.0 mol / L sodium citrate solution, 1.6 g of lithium carbonate, and 7.45 g of potassium hydroxide were mixed to form a sodium lithium potassium solution. The mixed sodium lithium potassium solution was dropped into the manganese nickel precipitate and mixed thoroughly. The mixture was dried in an oven at 100°C for 45 min, ball milled, and calcined at 680°C in a tubular heater for 7 h and 7 min to obtain a sodium ion positive electrode material Na(Li 0.053 K 0.053 Ni 0.164 Mn 0.73 ) 2 .

[0075] (2) Weigh 20 g of sodium ion positive electrode material Na(Li 0.053 K 0.053 Ni 0.164 Mn 0.73 ) 2 The mixture was added into 30 mL of methanol (ammonia content: 0.57%) and mixed evenly. The mixture was sent to a tubular heater, vented, introduced with Ar, and kept warm at 240°C for 3 h and 15 min. The mixture was cooled to room temperature, washed, demagnetized, and dried to obtain a surface-reduced sodium ion positive electrode material.

[0076] (3) 20 mL of 16.4 w% salicylic acid and 20 mL of propylene glycol were fully stirred, and 8 mL of 0.07 mol / L zinc nitrate solution was added dropwise. The mixture was stirred, allowed to stand for 4 h and 7 min, and centrifuged. The mixture was sent to a microwave reactor, and the gas in the reactor was evacuated. The mixture was dried at 80 °C and dehydrated for 70 min to obtain Zn-C-based nanomaterials.

[0077] (4) 10 g of the surface-reduced sodium ion positive electrode material was mixed with 0.24 g of Zn-C-based nanomaterial, ball-milled, and sent to a tubular heater, and calcined at 570° C. in an air atmosphere for 7 h 31 min, cooled, washed, and dried in an oven at 100° C. for 3 h 2 min to obtain Na(Li 0.053 K 0.053 Ni 0.164 Mn 0.73 ) 2 @Zn-C material.

[0078] Example 5

[0079] The sodium ion positive electrode material of this embodiment has the formula Na(Li 0.10 K0.04 Ni 0.46 Mn 0.40 ) 2 @Zn-C.

[0080] The preparation method of the sodium ion positive electrode material of this embodiment has the following specific steps:

[0081] (1) 150 mL of 1.07 mol / L manganese sulfate solution and 498 mL of 0.37 mol / L nickel sulfate solution were mixed in a polytetrafluoroethylene cup, and then placed in a 50°C water bath and stirred. 430 mL of 0.30 mol / L ammonium carbonate was added dropwise until complete precipitation to obtain a manganese nickel precipitate. The precipitate was separated, and 420 mL of 1.0 mol / L sodium citrate solution, 0.96 g of lithium hydroxide, and 0.90 g of potassium hydroxide were mixed to form a sodium lithium potassium solution. The sodium lithium potassium solution was added dropwise to the manganese nickel precipitate and mixed thoroughly. The mixture was dried in an oven at 100°C for 45 min, ball milled, and calcined at 680°C in a tubular heater for 7 h and 7 min to obtain a sodium ion positive electrode material Na(Li 0.10 K 0.04 Ni 0.46 Mn 0.40 ) 2 .

[0082] (2) Weigh 20g Na(Li 0.10 K 0.04 Ni 0.46 Mn 0.40 ) 2 The mixture was added into 30 mL of methanol (ammonium sulfate content: 0.89%) and mixed evenly. The mixture was sent to a tubular heater to exhaust gas, and Ar was introduced. The mixture was kept at 340°C for 2 h and 11 min, cooled to room temperature, washed, demagnetized, and dried to obtain a surface-reduced sodium ion positive electrode material.

[0083] (3) 25 mL of 32.7 w% salicylic acid and 25 mL of propylene glycol were fully stirred, and 10 mL of 0.07 mol / L zinc nitrate solution was added dropwise, stirred, allowed to stand for 4 h and 4 min, centrifuged, and sent to a microwave reactor. The gas in the reactor was evacuated, and the temperature was set to 86 ° C for drying and dehydration for 60 min to obtain Zn-C-based nanomaterials.

[0084] (4) 10 g of the surface-reduced sodium ion positive electrode material was mixed with 0.6 g of Cu-C-based nanomaterial, ball-milled, and sent to a tubular heater. The mixture was calcined at 570° C. in an air atmosphere for 7 h and 31 min, cooled, washed, and dried in an oven at 100° C. for 3 h and 2 min to obtain Na(Li 0.10 K 0.04 Ni 0.46 Mn 0.40 ) 2 @Zn-C material.

[0085] Comparative Example 1

[0086] The sodium ion positive electrode material of this comparative example has the formula Na(Li 0.208 Ni 0.192 Mn 0.60 ) 2 .

[0087] The preparation method of the sodium ion positive electrode material of this comparative example comprises the following specific steps:

[0088] (1) 200 mL of 1.5 mol / L manganese sulfate solution and 208 mL of 0.37 mol / L nickel sulfate solution were mixed in a polytetrafluoroethylene cup, the polytetrafluoroethylene cup was placed in a 50°C water bath, and stirred. 230 mL of 1.45 mol / L ammonium was added dropwise until complete precipitation to obtain a manganese-nickel precipitate. The precipitate was separated, and 240 mL of 1.73 mol / L sodium hydroxide solution and 1.3 g of potassium hydroxide were mixed to form a sodium-potassium solution. The sodium-potassium solution was added dropwise to the manganese-nickel precipitate, and the mixture was fully mixed, dried in an oven at 95°C for 40 min, ball-milled, and calcined at 750°C in a tubular heater for 7 h and 33 min to obtain a sodium ion positive electrode material Na(K 0.058 Ni 0.192 Mn 0.75 ) 2 .

[0089] Comparative Example 2

[0090] The sodium ion positive electrode material of this comparative example has the formula of NaNiMnO 2 @Cu-C.

[0091] The preparation method of the sodium ion positive electrode material of this comparative example comprises the following specific steps:

[0092] (1) 100 mL of 0.75 mol / L manganese sulfate solution and 120 mL of 0.63 mol / L nickel sulfate solution were mixed in a polytetrafluoroethylene cup, the polytetrafluoroethylene cup was placed in a 50°C water bath, and stirred. 260 mL of 0.30 mol / L ammonium carbonate was added dropwise until complete precipitation to obtain a manganese-nickel precipitate. The precipitate was separated, and 110 mL of 1.0 mol / L sodium citrate solution and 10 mL of 0.13 mol / L were added dropwise to the manganese-nickel precipitate, and the mixture was fully mixed. The mixture was dried in an oven at 95°C for 45 min, ball-milled, and calcined at 550°C in a tubular heater for 7 h and 33 min to obtain NaNiMnO 2 .

[0093] (2) 25 mL of 32.7 w% salicylic acid and 25 mL of propylene glycol were fully stirred, and 10 mL of 0.05 mol / L copper nitrate solution was added dropwise. The mixture was stirred, allowed to stand for 4 h and 4 min, and centrifuged. The mixture was sent to a microwave reactor, and the gas in the reactor was evacuated. The reactor was dried at 86 °C and dehydrated for 60 min to obtain Cu-C-based nanomaterials.

[0094] (3) Take 10gNaNiMnO 2 It was mixed with 0.3 g Cu-C-based nanomaterials, ball-milled, sent to a tubular heater, calcined at 660 ° C in an air-filled atmosphere for 7 h and 33 min, cooled, washed, and dried in an oven at 95 ° C for 3 h and 23 min to obtain NaNiMnO 2 @Cu-C material.

[0095] Analysis of Examples 1-5 and Comparative Examples 1-2:

[0096] The sodium ion positive electrode material, carbon black conductive agent, and PVDF in Example 1-5 and Comparative Example 1-2 were prepared into a slurry in a mass ratio of 80:15:5, and then coated on copper foil to prepare a pole piece, which was placed in an oven and dried at 80°C. The sodium flakes were used as the counter electrode. The electrolyte was 1.5M sodium hexafluorophosphate in propylene carbonate, Celgard2400 was used as the diaphragm, and the battery was assembled in a vacuum glove box under an argon atmosphere. The cycle performance was tested using an electrochemical workstation, and the current density of the test was 250mAh·g -1 The charge and discharge range is 2.5~3.5V, and the test temperature is 25℃.

[0097] Table 1 Battery test data obtained from positive electrode materials prepared in Examples 1-5 and Comparative Examples 1-2

[0098]

[0099] Table 1 Density and specific surface area of ​​positive electrode materials prepared in Examples 1-5 and Comparative Examples 1-2

[0100]

[0101] In Table 1, the first, 100th, and 200th discharge specific capacities of the batteries obtained from the positive electrode materials prepared in Examples 1-5 are in the range of 145.8-152.7 mAh·g -1 , which are higher than the first, 100th, and 200th discharge specific capacities of the battery obtained by the positive electrode material prepared in Comparative Examples 1-2 (142.7, 143.5 mAh·g -1), the positive electrode materials of Examples 1-5 are treated with surface reduction by adding a low proportion of ammonia to methanol, and MC-based nanomaterials are added to inhibit the peeling of the oxide layer, reduce the structural phase change of the material during charging and discharging, and the material performance is better; compared with Comparative Example 1 without the addition of Cu-C-based nanomaterials, Comparative Example 2 has higher coulombic efficiency for the first, 100th, and 200th discharges, and better performance.

[0102] In Table 2, the tap density of the positive electrode materials prepared in Examples 1-5 is 3.42 m 3 ·g -1 、3.48m 3 ·g -1 、3.42m 3 ·g -1 、3.47m 3 ·g -1 、3.44m 3 ·g -1 , while the tap density of the positive electrode material prepared in Comparative Example 1-2 is 3.27m 3 ·g -1 、3.34m 3 ·g -1 , the tap density is lower; the specific surface areas of the positive electrode materials prepared in Examples 1-5 are 0.54m 2 ·g -1 、0.56m 2 ·g -1 、0.58m 2 ·g -1 、0.57m 2 ·g -1 、0.58m 2 ·g -1 , while the 0.49m 2 ·g -1 、0.52m 2 ·g -1 , the specific surface area is lower, and compared with the comparative example 1 which is not doped with Cu-C based nanomaterials, the comparative example 2 has higher tap density and specific surface area.

[0103] Figure 1 This is a SEM image of the Co-C based nanomaterial prepared in Example 1 of the present invention; Figure 2 This is the SEM image of the Cu-C based nanomaterial prepared in Example 4 of the present invention. Figure 1 and Figure 2 In the available, Figure 1 Co-C based nanomaterials, Figure 2 The size of Cu-C based nanomaterials is between 0.2-5μm and in fragmented form, with the majority being between 0.5-2μm.

[0104] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A method for preparing a sodium ion positive electrode material, characterized in that: The following steps are involved: Mix manganese salt and nickel salt, add precipitant, react, separate solid and liquid, take solid phase, add sodium potassium or sodium lithium solution, mix, sinter, and obtain Na(Z k Ni t Mn f )O2; The Na(Z k Ni t Mn f )O2 is added to methanol containing an ammonium source and mixed to perform surface reduction to obtain a surface-reduced sodium ion positive electrode material; The surface-reduced sodium ion positive electrode material is mixed with the MC-based nanomaterial, and calcined to obtain the sodium ion positive electrode material; The proportion of ammonium source in the methanol containing ammonium source is 0.001-5%; The general formula of the sodium ion cathode material is Na(Z k Ni t Mn f )O2 / M-C, where k + t + f = 1, 0 < k ≤ 0.3, 0 < t ≤ 0.5, 0.4 ≤ f < 1, and Z is at least one of K and Li; M is at least one of Cu and Zn.

2. The preparation method according to claim 1, characterized in that: The general formula of the sodium ion cathode material is Na(Z k Ni t Mn f )O2 / M-C, where k + t + f = 1, 0 < k ≤ 0.25, 0.15 ≤ t ≤ 0.5, 0.4 ≤ f ≤ 0.8, and Z is at least one of K and Li; M is at least one of Cu and Zn.

3. The preparation method according to claim 1, characterized in that: The sodium ion positive electrode material is Na(K 0.058 Ni 0.192 Mn 0.75 )O2@Cu-C、Na(K 0.208 Ni 0.192 Mn 0.60 )O2@Cu-C、Na(K 0.117 Ni 0.233 Mn 0.65 )O2@Zn-C、Na(Li 0.053 K 0.053 Ni 0.164 Mn 0.73 )O2@Zn-C、Na(Li 0.10 K 0.04 Ni 0.46 Mn 0.40 )One of the O2@Zn-C.

4. The preparation method according to claim 1, characterized in that: The manganese salt is at least one of manganese sulfate, manganese nitrate and manganese chloride; the nickel salt is at least one of nickel sulfate, nickel nitrate and nickel chloride; the precipitant is at least one of sodium carbonate, lithium carbonate and carbonic acid.

5. The preparation method according to claim 1, characterized in that: The sodium-potassium or sodium-lithium solution is obtained by dissolving a sodium source, a potassium source or a lithium source in water; the sodium source is at least one of sodium hydroxide, sodium acetate, sodium carbonate, sodium phosphate, sodium citrate and sodium oxalate; the lithium source is at least one of lithium hydroxide, lithium formate, lithium acetate, lithium carbonate, lithium nitrate, lithium oxalate, lithium sulfate or lithium chloride; the potassium source is at least one of potassium hydroxide, potassium formate, potassium acetate, potassium carbonate, potassium nitrate, potassium oxalate, potassium sulfate or potassium chloride.

6. The preparation method according to claim 1, characterized in that: The MC-based nano material is prepared by mixing a complexing agent and a polar organic matter, and then adding the mixture dropwise into a solution containing M ions, stirring the mixture, standing the mixture, centrifuging the mixture, and drying the mixture to obtain the MC-based nano material.

7. The preparation method according to claim 6, characterized in that: The complexing agent is at least one of salicylic acid and terephthalic acid; the polar organic matter is at least one of ethylene glycol, acetone, acetic acid and petroleum ether.

8. A battery, characterized in that: It comprises a sodium ion positive electrode material prepared by the method for preparing a sodium ion positive electrode material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • High-nickel ternary positive electrode material and preparation method thereof

    CN111924894A

  • Active material, manufacturing method thereof and nonaqueous electrolyte secondary battery containing the material

    CN1694286A

  • Lithium and sodium containing layered oxide material, cathodes and sodium ion electrochemical cells

    US20160218363A1